Fostering Collaborative Leadership Through Playbuilding. Issue 156 (7th December 2017) - Bishop, Kathy; Weigler, Will; Lloyd, Tracey; Beare, David
Abstract: Playbuilding is one response to the search for creative ways to approach leadership and learning. Drawing upon their practical experiences within community‐based, secondary school, and university settings, the authors share stories and strategies for fostering collaborative leadership through playbuilding.